TINDAK PIDANA KORUPSI DALAM PENYUSUNAN APBD - Saryono Hanadi; M.I. Wiwik Yuni Hastuti; Alef Musyahadah Rahmah (Komisi Yudisial RI, 2010)
ABSTRACTThis article elaborates the Court Verdict Number 76/Pid./B/2008/PN.Pwt concerning on the case of corruption in APBD of Banyumas in 2003, which was conducted by its member of the DPRD . In this case, the prosecutors accused the defendants jointly conducting an on going act of corruption. The judges decided that the defendants were not accountable for their unlawful activity. Considering the defendants were just as the proposer of the budget in this matter, the court thus released them from all the prosecutions (van onslag of alle rechtsvervolging). There is a particular relationship between the board members regarding the budget proposal which was assumed to be deviated from the budget approved by the head of the region. It resulted in the release of these regulations. We cannot well thought-out where the fault is until we can find the connection with each other, which is the conducts of the participants that appear in the link as a unity.Keywords: corruption of APBD, medeplegen, onslag van alle rechtsvervolging, criminal act. ABSTRAKArtikel ini mengelaborasi Putusan Pengadilan Nomor 76/Pid./B/2008/PN.Pwt terkait dengan kasus korupsi APBD Banyumas tahun 2003, yang dilakukan oleh Anggota DPRD. Dalam kasus ini, jaksa menuntut terdakwa bersama-sama melakukan korupsi. Hakim memutuskan bahwa terdakwa menjalankan anggaran yang menyimpang. Pertimbangan terdakwa hanya mengajukan anggaran sehingga meminta pengadilan untuk melepaskan dari semua dakwaan, van onslag of alle rechtsvervolging. Dalam kasus ini terdapat keterkaitan anggota DPRD untuk melakukan pengawasan dan mensetujui anggaran yang diajukan oleh pemerintah sehingga keduanya bersama-sama melahirkan peraturan daerah. Oleh sebab itu, kita tidak bisa mengambil kesimpulan dimana letak kesalahannya hingga mendapatkan keterkaitan satu dengan yang lain karena merupakan satu kesatuan jaringan.Kata kunci: korupsi APBD, turut serta, membebaskan para terdakwa dari segala tuntutan hukum, UU kejahatan.